2005
DOI: 10.4310/ajm.2005.v9.n1.a6
|View full text |Cite
|
Sign up to set email alerts
|

Closed Minimal Willimore Hypersurfaces of <b>S</b><sup>5</sup>(1) with Constant Scalar Curvature

Abstract: We consider minimal closed hypersurfaces M 4 ⊂ S 5 (1) with constant scalar curvature. We prove that, if M 4 is additionally a Willmore hypersurface, then it is isoparametric. This gives a positive answer to the question made by Chern about the pinching of the scalar curvature for closed minimal Willmore hypersurfaces in dimension 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…By using exactly the same methods of proof as in Lusala-Scherfner-Sousa (cf. [13]) we have the following inequality…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…By using exactly the same methods of proof as in Lusala-Scherfner-Sousa (cf. [13]) we have the following inequality…”
Section: )mentioning
confidence: 99%
“…We want to point out that Chern's conjecture mentioned above is still unsolved for n ≥ 4. An interesting result, recently published (see [13]), gives a partial answer for the case n = 4. It is due to T. Lusala, M. Scherfner and L. A. M. de Sousa Jr. and reads: Theorem 1.4.…”
Section: Introductionmentioning
confidence: 99%
“…The method of [dB90] was taken to deal with 4 and 6 dimensional cases. In the case n = 4, Lusala-Scherfner-Sousa [LSS05] showed that a closed, minimal, Willmore hypersurface M 4 of S 5 with non-negative constant scalar curvature is isoparametric. Denoting the r-th power sum of principal curvatures by f r , the Willmore condition for minimal hypersurfaces with constant scalar curvature is equivalent to the condition that f 3 = 0.…”
Section: Introductionmentioning
confidence: 99%
“…For n 4, the Chern conjecture remains open, although some partial result exist for low dimensions and with additional conditions for the curvature functions, such as: Theorem 1.1. [8] Let M 4 be a closed minimal Willmore hypersurface in S 5 with constant nonnegative scalar curvature. Then M 4 is isoparametric.…”
Section: Introductionmentioning
confidence: 99%